2013
DOI: 10.1371/journal.pone.0063831
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Concentration Is Not Associated with Increased Mortality and Morbidity after Cardiac Surgery

Abstract: ObjectiveTo determine the effect of vitamin D on postoperative outcomes in cardiac surgical patients.DesignRetrospective study.SettingSingle institution-teaching hospital.ParticipantsAdult cardiac surgical patients with perioperative 25-hydroxyvitamin D measurements.InterventionsNone. We gathered information from the Cardiac Anesthesiology Registry that was obtained at the time of the patients’ visit/hospitalization.Measurements and Main ResultsWe used data of 18,064 patients from the Cardiac Anesthesiology Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…[ 32 ] coronary bypass graft, valve replacement prospective, observational 70 59 no 25(OH)D, RIA, and 1,25-(OH) 2 D, ELISA continuous 30 days increased risk for composite in-hospital mortality, myocardial infarction, low cardiac output syndrome, infection, and stroke, decreased glomerular filtration rate Zittermann et al [ 33 ] cardiac transplant and non-transplant cardiac surgery prospective, observational not reported 208 no 25(OH)D, RIA, and 1,25-(OH) 2 D, ELISA continuous 30 days decreased glomerular filtration rate Turan et al . [ 34 ] cardiac surgery retrospective not reported 426 yes 25(OH)D, not reported continuous 30 days none Zittermann et al . [ 35 ] non-transplant cardiac surgery prospective, observational 70 4418 no 25(OH)D, RIA categorical, <12, 12–20, 20–30, 30–40, >40 ng/mL thresholds 12 months increased risk of in-hospital mortality, myocardial infarction, low cardiac output syndrome, stroke, 6 and 12 month mortality; U-shaped risk for prolonged ventilatory support and intensive care unit (ICU) stay Zittermann et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 32 ] coronary bypass graft, valve replacement prospective, observational 70 59 no 25(OH)D, RIA, and 1,25-(OH) 2 D, ELISA continuous 30 days increased risk for composite in-hospital mortality, myocardial infarction, low cardiac output syndrome, infection, and stroke, decreased glomerular filtration rate Zittermann et al [ 33 ] cardiac transplant and non-transplant cardiac surgery prospective, observational not reported 208 no 25(OH)D, RIA, and 1,25-(OH) 2 D, ELISA continuous 30 days decreased glomerular filtration rate Turan et al . [ 34 ] cardiac surgery retrospective not reported 426 yes 25(OH)D, not reported continuous 30 days none Zittermann et al . [ 35 ] non-transplant cardiac surgery prospective, observational 70 4418 no 25(OH)D, RIA categorical, <12, 12–20, 20–30, 30–40, >40 ng/mL thresholds 12 months increased risk of in-hospital mortality, myocardial infarction, low cardiac output syndrome, stroke, 6 and 12 month mortality; U-shaped risk for prolonged ventilatory support and intensive care unit (ICU) stay Zittermann et al .…”
Section: Resultsmentioning
confidence: 99%
“…Five publications observed no significant difference in the incidence of adverse outcomes between groups with lower and higher vitamin D status [ 11 , 14 , 15 , 17 , 34 ]. However, in none is it clear that no difference truly exists, or if design and conduct constraints preclude detection of a correlation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a study of 3371 patients undergoing coronary artery bypass grafting or valve surgery, 25‐OH vitamin D was inversely associated with postoperative cardiac complications including in‐hospital death, myocardial infarction, low output syndrome, and stroke . In contrast, other studies have not found associations with postoperative mortality or cardiac comorbidities (eg, arrhythmias, low cardiac output) in cardiac surgery patients, perhaps because of small sample sizes and presence of competing risk factors. Interestingly, serum 25‐OH and 1,25 (OH) 2 vitamin D fluctuate during hospital stays and following cardiac surgery, likely due to fluid administration.…”
Section: Discussionmentioning
confidence: 95%
“…9 As such, 25-OH vitamin D could still be valuable as a clinical prognostic marker. 8,[10][11][12] While several clinical studies have evaluated the association between 25-OH vitamin D and risk of CVD outcomes, complications, and mortality following surgery or hospitalization, [13][14][15][16][17][18][19][20] few have fully evaluated the prognostic value of 25-OH vitamin D by contrasting model discrimination, fit, and calibration to those from models containing established risk factors. Furthermore, none have examined the ability of 25-OH vitamin D to appropriately reclassify patient risk when added to models containing established risk factors.…”
mentioning
confidence: 99%